TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PENERAPAN SAK ETAP - Nadia Eka Famila; Sri Dwi Estiningrum (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to obtain empirical the effect of education level, understanding of accounting, and utilization of information technology on the application of Financial Accounting Standards for Entities without Public Accountability (FAS-EWPA/ SAK ETAP) based on computerization. The object in this study is cooperatives in Kedungwaru District, Tulungagung Regency, which totals 136 units. A questionnaire was selected either through a paper-based survey questionnaire or an online survey so that information is obtained in the form of primary data. The research method used is quantitative associative with multiple regression analysis using the SPSS 26 tool. The results of this study indicate that education level and utilization of information technology partially affect the application of computerized-based SAK ETAP, while accounting understanding partially does not affect the application of computerized-based SAK ETAP. Simultaneous testing shows that education level, accounting understanding, and utilization of information technology affect the application of computerized-based SAK ETAP.